2009
DOI: 10.1016/j.ecolind.2008.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale approach using phytoplankton as a first step towards the definition of the ecological status of reservoirs

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 29 publications
3
26
0
Order By: Relevance
“…There are, however, cases for which paleolimnology alone is inadequate to decipher linkages between watershed alterations and lacustrine ecological processes (Saros 2009). Recently there has been an appeal to integrate neo-and paleolimnological methods to discern relationships between watershed changes and ecological processes, and to use historical chemical data to validate paleolimnological results (Battarbee et al 2005;Saros 2009;Cabecinha et al 2009;Woodridge et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, cases for which paleolimnology alone is inadequate to decipher linkages between watershed alterations and lacustrine ecological processes (Saros 2009). Recently there has been an appeal to integrate neo-and paleolimnological methods to discern relationships between watershed changes and ecological processes, and to use historical chemical data to validate paleolimnological results (Battarbee et al 2005;Saros 2009;Cabecinha et al 2009;Woodridge et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This extensive geographic area represents a wide range in physical and chemical characteristics, soil use and anthropogenic pressure, including both good and poor water quality conditions. A recent analysis of these data showed that phytoplankton community composition differed markedly between high altitude and lowland reservoirs (Cabecinha et al, 2009); hence, these two reservoir groups were analysed separately here. The two groups comprise: Type 1-lowland ''run-of-river'' reservoirs located in the main rivers (Douro and Tagus), with a very short residence time (n = 10); Type 2-deeper high altitude reservoirs, largely located in tributaries, with long residence time (n = 24) (Fig.…”
Section: Study Areamentioning
confidence: 99%
“…The sampling periodicity was carried out on an annual base for 58% of the reservoirs. The remaining reservoirs were visited biannually (27%) and triennially (15%) (Cabecinha et al, 2009). All the samples were collected at 100 m from the reservoirs's crest, at two different depths: (a) near the surface (approximately 0.5 m depth); and (b) near the bottom (2 m above bottom, only for environmental parameters and chlorophyll a).…”
Section: Environmental Parameters and Chlorophyll Amentioning
confidence: 99%
“…Due to their short life cycle, planktonic algae are sensitive to respond quickly to a broad range of stressors, and thus an ideal indicator for water quality (Domingues and Galva˜o, 2007;Cabecinha et al, 2009). The investigation of the phytoplankton community has become an important part of the overall waterquality monitoring (Majaneva et al, 2009).…”
Section: Introductionmentioning
confidence: 99%